TINGKAT PEMENUHAN INFORMASI MITIGASI PENANGGULANGAN BENCANA MELALUI ILM PADA LPP TVRI BALI - I NENGAH MULIARTA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
ABSTRACTTVRI is a public broadcasting institution that in its broadcasting process uses public frequencies and itsoperations use public funds through budget allocations from the government. As a public broadcastinginstitution, TVRI has an obligation to provide education and information to the public. This obligation, oneof which can be done through broadcasts that are carried out in the form of public service advertisements(PSA). This study aims to determine the level of fulfillment of the spread of disaster mitigation through PSAcarried out by TVRI Bali, so that future plans can be made to maximize the spread of disaster mitigationthrough PSA. The research was conducted by taking data from the TVRI Bali program during October toDecember 2018. The results showed that TVRI Bali had not fulfilled information related to disastermitigation, as evidenced by the absence of public service advertisements produced and broadcast related todisaster mitigation. In general, TVRI Bali has not met the minimum percentage of PSA broadcastingcompliance in accordance with the Broadcasting Law, Broadcasting Behavior Guidelines (BBG) andBroadcast Program Standards (BPS). Keywords: Mitigation, Disaster Management, PSA, Broadcasting Institutions, TVRI